Dietary choline in gonadectomized kittens improved food intake and body composition but not satiety, serum lipids, or energy expenditure - Godfrey, Hannah; Rankovic, Alexandra; Grant, Caitlin E.; Shoveller, Anna Kate; Bakovic, Marica; Abood, Sarah K.; Verbrugghe, Adronie (PLOS ONE, 2022)
Gonadectomy is a major risk factor for feline obesity. The lipotropic effects of choline have demonstrated benefits for growth and carcass composition in livestock. The consumption of supplemental choline on body weight (BW), body composition, lipid metabolism, energy expenditure (EE), and serum satiety hormones were evaluated in 15 gonadectomized male kittens. Kittens were offered a base diet formulated for growth (3310mg choline/kg dry matter [DM]) to daily energy requirements (DER) over an 11-week acclimation. Post-gonadectomy, kittens were assigned to a base diet (CONTROL, n = 7) or choline group (base diet with additional choline at 300mg/kg BW0.75 as a top dress) (CHOLINE, n = 8). For 12-weeks post-neuter, kittens were offered three times their DER over three meals to mimic ad libitum feeding. At week -1 and 12, body composition was assessed using dual energy x-ray absorptiometry (DXA), 24-hour indirect calorimetry was performed for EE and respiratory quotients (RQ), and fasted serum samples were analyzed for lipid compounds and satiety hormones. Daily food intake (FI) and weekly BW were measured. Data was analyzed as a repeated measures of variance (ANCOVA) using the GLIMMIX procedure with time and group as fixed effects. CHOLINE had lower mean daily FI and lower rates of BW accretion (P<0.05) in contrast to CONTROL. All absolute body composition data increased over time for both groups, with lower increases in total tissue mass (P = 0.031) and fat mass (P = 0.005) in CHOLINE. Serum satiety hormones and lipid compounds did not differ (P>0.05) between groups, but both groups experienced a decrease in low-density lipoproteins and increase in high-density lipoproteins (P<0.05). Primary substrate utilization showed lipid use when fasted and use of protein or mixed macronutrients in the fed state. Fed state EE decreased post-gonadectomy (P = 0.004), however, CHOLINE did not affect total EE or RQ. These results suggest that supplemental dietary choline reduces FI, BW, and fat mass and may help to reduce the propensity of weight gain and subsequent obesity in gonadectomized feline populations.